Chicken endothelial cells are highly responsive to viral innate immune stimuli and are susceptible to infections with various avian pathogens. Issue 2 (4th March 2019) - Lion, Adrien; Esnault, Evelyne; Kut, Emmanuel; Guillory, Vanaïque; Trapp-Fragnet, Laetitia; Soubies, Sébastien M.; Chanteloup, Nathalie; Niepceron, Alisson; Guabiraba, Rodrigo; Marc, Daniel; Eterradossi, Nicolas; Trapp, Sascha; et al.
ABSTRACT : It is well established that the endothelium plays a prominent role in the pathogenesis of various infectious diseases in mammals. However, little is known about the role of endothelial cells (EC) as targets for avian pathogens and their contribution to the pathogenesis of infectious diseases in galliform birds. First, we explored the innate immune response of primary chicken aortic endothelial cells (pchAEC), obtained from 18-day-old embryos, to stimulation with pathogen-associated molecular patterns or recombinant chicken interferons (type I, II and III IFNs). In spite of the abundant expression of a number of innate immune receptors, marked cytokine responses to stimulation with pathogen-associated molecular patterns were only seen in pchAEC treated with the TLR3 agonist polyI:C (pI:C) and the MDA5 agonist liposome-complexed polyI:C (L-pI:C), as was assessed by quantitative PCR and luciferase-based IFN-I/NFκB reporter assays. Treatments of pchAEC with IFN-α, IFN-γ and IFN-λ resulted in STAT1-phosphorylation/activation, as was revealed by immunoblotting. Next, we demonstrated that pchAEC are susceptible to infection with a variety of poultry pathogens, including Marek's disease virus (MDV), infectious bursal disease virus (IBDV), avian pathogenic Escherichia coli (APEC) and Eimeria tenella . Our data highlight that chicken EC are potential targets for viral, bacterial and protozoan pathogens in gallinaceous poultry and may partake in the inflammatory and antimicrobial response. The pchAEC infection model used herein will allow further studies interrogating avian pathogen interactions with vascular EC. RESEARCH HIGHLIGHTS: Use of a well-defined primary chicken aortic endothelial cell (pchAEC) culture model for studying avian host–pathogen interactions. pchAEC are responsive to innate immune stimulation with viral pathogen-associated molecular patterns and chicken type I, II and III interferons. pchAEC are susceptible to infections with economically important poultry pathogens, including MDV, IBDV, APEC and Eimeria tenella.